Variability in Phytophthora drechsieri f.sp. cajani in response to host differentials and fungicides - and S.C. DUBEY*, BIRENDRA SINGH (Indian Phytopathology, 2005)
Seven differential hosts of pigeonpea distinguished population of P. drechsleri t.sp. cajani isolated from Delhi (PP-1), Bihar (PP-8), Uttar Pradesh (PP-2, 3, 4, 5 and 9 ) and Uttranchal (PP-6 and 7) into four variable groups as least aggressive (group-I; PP-1, 2 and 3), virulent (group-II; PP-4 and 5), moderately virulent (group-III; PP-6 and 7) and highly virulent (group-IV; PP-8 and 9). Individually, Pusa (Bihar) isolate PP-8 proved most virulent and isolate PP-2 from Ghaziabad (Uttar Pradesh) was least virulent. Variable sensitivity to apron 35 WS, rldornll MZ-72 WP and captafol 80 WP fungitoxicants among four selected isolates of P. drechsleri f.sp. cajani was noticed. Delhi isolate (PP-1) was tolerant to captafol with highest EC so (15.11 ,.,g a.i./ml) value whereas, Pantnagar isolate (PP-6) was highly sensitive with EC so (2.14 ,.,g a.i./ml). Kanpur isolate (PP-4) exhibited most tolerance to rldornll MZ-72 WP. In the case of apron 35 WS, Delhi isolate (PP-1) was most sensitive. Thus, the present studies showed the possibility of existence of four races of the pathogen in north India.